Evaluation of the Reproductive Performance of African Catfish (Clarias Gariepinus) Brood Stock Fed on Three Locally Manufactured Commercial Feeds - Ondhoro, Constantine Chobet; Mwanja, Mathew Tenywa; Nkambo, Mujibu; Kamahooro, Immaculate; Aruho, Cassius (International Journal of Fisheries and Aquatic Studies, 2013)
Brood stock management experiment was conducted at Kireka fish farm Uganda, to evaluate the fecundity and economic performance of three new local commercial feeds for African catfish brood stock development and conditioning. The fish were conditioned in earthen ponds, stocked at 0.5 kg/m3 for three months before spawning. The feeds were code named N2, B3 and N3 for Kajjansi 35%, Ugachick 35% and Tende Innovative Farm feeds respectively. Results indicated that there was no significant difference in the crude protein composition of all the test diets. Significantly lower lipid contents (2.326%) were noticed in N3. Mean number of eggs per unit brood stock weight differed significantly across all feed treatment (F = 10.179, P= 0.002), with N2 producing the highest N = 57,075± 18,922; B3= 51,477±16,266; N3= 45,375±13,399, generally improved from the baseline of 6,874±1001. Fertilization was significantly different (F=3.695E30, P=0.0001), across all diets (Mean; (N2= 78.13±8.99%; B3= 72.93±16.02%; N3= 59.95±19.96%). Hatchability differed significantly across all feed treatments (F=3.6E31, P=0.0001), compared to the baseline, Mean; (N2= 77±10.01%; B3= 67± 2.5%; N3= 58±11.15%; baseline= 45.80±5.45%). It was established that a farmer using N2 (Kajjansi) feeds would generate up to $1,114 net profit per kilogram of female brood stock spawned. While using B3 (Ugachick 35%), would generate $196 per kilogram female above total cost. N2 was the best feed overall, with the highest fecundity, percent fertilization, hatchability & net returns above total cost, followed by B3 and lastly N3. The findings of this study show that, though the profitability of a hatchery business depends on management and the germplasm, fecundity plays a crucial role in determining the net returns of the business and is greatly affected by type and quality of brood stock feeds.
Keywords: African catfish; brood stock feeds; net returns; hatchability